2013
DOI: 10.3892/or.2013.2906
|View full text |Cite
|
Sign up to set email alerts
|

Levels of cell-free DNA and plasma KRAS during treatment of advanced NSCLC

Abstract: Abstract. Non-small cell lung cancer (NSCLC) is one of the most common malignant tumours in the Western world and is associated with a poor prognosis. Biomarkers predicting prognosis and therapeutic effects are highly required, and cell-free DNA (cfDNA) may be a feasible option. Genetic mutations can be analysed in plasma and may increase the scientific use of such measurements. In the present study, we investigated: i) the dynamics of cfDNA and plasma mutated KRAS (pmKRAS) during the treatment of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, these studies were often small and reported varying results. Some of them showed that a higher cfDNA concentration was associated with poorer survival in NSCLC patients [19, 20], whereas other studies failed to demonstrate such correlation [21, 22]. On the other hand, several studies had analyzed the association between genotype detected in cfDNA with treatment response or survival in NSCLC [2326].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were often small and reported varying results. Some of them showed that a higher cfDNA concentration was associated with poorer survival in NSCLC patients [19, 20], whereas other studies failed to demonstrate such correlation [21, 22]. On the other hand, several studies had analyzed the association between genotype detected in cfDNA with treatment response or survival in NSCLC [2326].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with distant metastases have a significantly higher level of cfDNA compared to patients without metastases. Total mutation-specific cfDNA decreases during treatment but the levels increase later on in patients with recurrence [25,26].…”
Section: Cell Free Dna (Cfdna)mentioning
confidence: 99%
“…Current procedures for quantitative cfDNA analysis include simple spectrophotometry [100] and qPCR of housekeeping genes. Quantitation of both single genes like CYC [59], hTERT [61], β2 microglobulin [26,101], or multiple genes [82] in plasma samples has been used to quantitate cfDNA. Commercially available DNA DipStick TM Kit (Thermo Fisher Scientific) is, another, simple kit for qualitative assessment of cfDNA levels.…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
See 2 more Smart Citations